Endotracheal intubation versus supraglottic procedure in paediatric out-of-hospital cardiac arrest: a registry-based study. (November 2021) - Le Bastard, Quentin; Rouzioux, Jade; Montassier, Emmanuel; Baert, Valentine; Recher, Morgan; Hubert, Hervé; Leteurtre, Stéphane; Javaudin, François; ,
Abstract: Background: Out-of-hospital cardiac arrest (OHCA) in children is associated with a low survival rate. Conclusions in the literature are conflicting regarding the best way to handle ventilation. The purpose of this study was to assess the impact of two airway management strategies, endotracheal intubation (ETI) vs. supraglottic procedure, during cardiopulmonary resuscitation (CPR) on 30-day survival in paediatric OHCA. Methods: This was a retrospective, observational, multicentre, registry-based study conducted from July 2011 to March 2018. All paediatric OHCA patients under 18 years of age and managed by a mobile intensive care unit were included. The primary endpoint was 30-day survival in a weighted population (based on propensity scores). Results: Of 1579 children, 1355 (85.8%) received ETI and 224 (14.2%) received supraglottic ventilation during CPR. We observe a lower 30-day survival in the ETI group compared to the supraglottic group (7.7% vs. 14.3%, absolute difference, 6.6 percentage points; 95% confidence interval [CI], 2.3–12.0; propensity-adjusted odds ratio [paOR], 0.39; 95% CI, 0.25–0.62; p < 0.001), and also a poorer neurological outcome (paOR, 0.32; 95% CI, 0.19–0.54; p < 0.001). However, we did not identify any significant association between airway management strategy and return of spontaneous circulation (paOR, 1.15; 95% CI, 0.80–1.65; p = 0.46). Conclusions: The findings of this large cohort study suggest that ETI in paediatric OHCA, although performed by trained physicians, is associated with a worse outcome, regardless of traumatic or non-traumatic aetiology.